Perkembangan Teknologi Komunikasi dan Media Baru: Implikasi terhadap Teori Komunikasi - Novi Kurmia (MediaTor)
Technology development has shaped the way we communicate each other. New media also built a new mode of communication. These developments lead to a new map of communication—in the field of practice and theoretical domain. Responding to these developments, Ward divided media to ‘new’ news media, ‘new’ non-news media, and traditional media. Each was characterized by its technology, interactivity, and any other features. McQuail divided media into 4 type: interpersonal communication media, interactive playing media, information searching engine, and information exchange media such as Internet. For Pavlik, technical functions become the main feature of media categorization. There are stages of production and processing information, distribution and transmitting information, and display or ways of presenting information.